Thoracic Renal Artery - Rossi, Umberto G.; Rollandi, Gian Andrea (AORTA, 2019)
We report a case of right renal artery originating from the thoracic aorta with normal position of the right kidney. Although this anomaly is rare, vascular, thoracic, and urological surgeons should be aware about this vascular variant before planning their surgical intervention.
Keywords: renal artery; ectopic renal artery; computed tomography; vascular variant; aorta